Hypnobirthing as Self-Hypnosis in Reducing Anxiety Levels in Pregnant Women - Saida Muhamad; Anik Purwati (Jurnal Siti Rufaidah, 2025)
Pregnancy is a unique time in a woman's life and a valuable experience for a married couple. During pregnancy, women adjust to their pregnancy, and it's not uncommon for many to experience disappointment and anxiety due to hormonal influences and physical and psychological changes. Anxious pregnant women can experience negative consequences for themselves and their fetuses, such as increased blood pressure, preeclampsia, prematurity, low birth weight, and even the risk of maternal and fetal death. Hypnobirthing is a method for reducing anxiety and has no effect on fetal growth and development. The purpose of this study was to determine the effect of hypnobirthing as self-hypnosis in reducing anxiety in pregnant women. This study used a quasi-experimental design with a sample size of 50 participants. Data collection was conducted at Tidore City Regional Hospital. The variables used in this study were the level of anxiety of pregnant women as the dependent variable and hypnobirthing as the independent variable. Maternal anxiety levels were measured before and after hypnobirthing using the HARS questionnaire. Univariate and bivariate analyses (Wilcoxon sign test) were used for analysis. The results of the study showed that there was a difference in anxiety levels before and after hypnobirthing was given of 0.92 and there was a p-value of 0.0001, which means that there was a significant influence between hypnobirthing and reducing anxiety in pregnant women